2005
DOI: 10.1007/s10720-005-0064-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Electrical and Optical Properties of Sodium Nitrite and Sodium Nitrate Nanoparticles in Regular Porous Matrices

Abstract: New nanocomposites based on zeolites (NaA-NaNO 2 , NaA-NaNO 3 ) and opals (o-NaNO 2 , o-NaNO 3 ) that contain sodium nitrite or sodium nitrate nanoparticles in cages of regular porous matrices are prepared. The nanocomposites are characterized by scanning electron microscopy, diffuse reflectance spectroscopy, and electrical measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…35,36 Therefore the observed values of dissipation factor in the present films are reasonable. In general, the energy dissipation arises due to the resistive loss and/or pure dielectric loss.…”
Section: Dynamic Dielectric Constantsupporting
confidence: 77%
“…35,36 Therefore the observed values of dissipation factor in the present films are reasonable. In general, the energy dissipation arises due to the resistive loss and/or pure dielectric loss.…”
Section: Dynamic Dielectric Constantsupporting
confidence: 77%
“…Dielectric measurements have shown that nanostructured sodium nitrate (NaNO 3 ) demonstrates very high dielectric permittivity (like sodium nitrite) approaching melting temperature [9]. NaNO 3 is an ionic-molecular crystal with planar (as NaNO 2 ) anions NO − 3 but does not undergo ferroelectric PT.…”
Section: Introductionmentioning
confidence: 99%
“…The semi-empirical LCAO work of El-Dib and Hassan [8], for room temperature (293.15 K), found a band gap of 3.24 eV. The scanning electron microscopy, diffuse reflectance spectroscopy, and electrical measurements study of Balabinskaya et al [9], at a temperature of 300 K , reported an absorption edge of 3.0 eV.…”
Section: Introductionmentioning
confidence: 97%